Promoting Exercise and Healthy Diet Among Primary Care Patients: Feasibility, Preliminary Outcomes, and Lessons Learned From a Pilot Trial With High Intensity Interval Exercise - Smith-Ryan, Abbie E.; Weaver, Mark A.; Viera, Anthony J.; Weinberger, Morris; Blue, Malia N.M.; Hirsch, Katie R. (Frontiers in Sports and Active Living, 2021)
Physical activity and healthy diet are recognized as effective approaches for disease prevention. Controlled laboratory clinical trials support these approaches, yet minimal data exists supporting implementation of exercise as medicine within a healthcare setting. Objectives: To understand perception and barriers to exercise and nutrition from patients and physicians from a family medicine clinic (FMC) to inform the implementation of a laboratory-based exercise and nutrition lifestyle intervention (Phase I), and to determine the feasibility, adherence, and preliminary outcomes of implementing this lifestyle intervention into a FMC (Phase II). Methods: In phase I 10 patients and 5 physicians were interviewed regarding perceptions of exercise and nutrition practices. In phase II patients at risk for cardiovascular disease were enrolled into a lifestyle intervention (n = 16), within a FMC, manipulating diet and exercise. Cardiorespiratory fitness (CRF), body composition, and metabolic blood markers were completed at baseline, after the 12-week intervention, and at 24 weeks. Feasibility was defined by patients who completed the intervention and number of sessions vs. total available. Results: Prescribing high-intensity interval training and a meal replacement for 12 weeks in patients with at least one risk factor for cardiovascular disease, was shown to have moderate feasibility with 62.5% (n = 10) for patients completing the 12 week intervention, and poor feasibility for assessing effects 12 weeks after cessation of the intervention, with 50% (n = 5) participants returning. Tracking exercise electronically via FitBit had moderate fidelity (n = 9), with hardcopy logs yielding poor compliance (n = 6). This pilot study demonstrated preliminary effectiveness of this home-based approach for improving cardiorespiratory fitness with an average 4.31 ± 5.67 ml·kg·min−1 increase in peak oxygen consumption. Blood triglycerides and insulin were improved in 70% and 60% of the patients, respectively. Conclusions: Despite moderate feasibility, a home-based exercise and nutrition has the potential to be used as an effective approach for managing and mitigating cardiovascular disease risk factors. There were key lessons learned which will help to develop and adapt a larger scale lifestyle intervention into a clinical setting. Clinical Trial Registration:https://clinicaltrials.gov/ct2/show/study/NCT02482922, identifier NCT02482922.